SIMULATION MODEL OF NITROGEN-NITRATE (N-NO3-) DISTRIBUTION IN SHALLOW GROUNDWATER BASED ON CONTAMINANT LOADING ESTIMATION FROM SEPTIC TANK EFFLUENT AS A SOURCE (CASE STUDY: KRAMAT JATI SUB-DISTRICT, EAST JAKARTA) - Sari, Novita
Nitrogen is an essentials nutrient contained in domestic wastewater discharged through septic system. Nitrogen-Nitrate (N-NO3-) is a term of nitrogen transformation that has a harmful effect to human and environmental health. This contaminant is a conservative anorganic compound that travel with groundwater throughout flow direction. N-NO3- has a small impact of chemistry reaction and adsorption during its dissolved by groundwater. Through the issues of dangerous nitrate as a pollutant that would be consumed by the human, so in this research conducted distribution model of Nitrogen-Nitrate (N-NO3-) contamination in unconfined aquifer due to the septic tank effluent from dwellings. The simulation model will be established by six different scenarios based on the domestic activity and the presenc of existing N-NO3- in unconfined aquifer. Domestic activity devided into groundwater pumping and septic tank used by dwellings. Total groundwater debit pumping calculated 2527 - 4834 m3/day in Kramat Jati Sub-District as an initial parameter boundary condition in volumetric rate of groundwater abstraction. The estimaste of N-NO3- dissolved in groundwater attained 11.11 – 16.02 mg/liter. Groundwater flow simulation and N-NO3- transport simulated for 10 years with six scenarios applied. Every scenario model was built for observing the response of head and concentration as the impact of pumping and loading N-NO3- to groundwater. Result in simulation exhibited the groundwater pumping from resident didn’t give any significant effect of head change with the rate of head calculated 0.0054 – 0.0315 meter/year. All observation wells for concentration have the average rate between 0.05 – 1.2 mg/liter/year. The maximum displacement of the N-NO3- along 1600 meter from the place that have high concentration to low concentration. The depth of the contamination that has been exceed from water quality standard for applied simulation scenarios reach out 1 until 30 meter below surface to the groundwater level.